2000
DOI: 10.1111/j.1574-6941.2000.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of microbial communities in mobile deltaic muds of Southeastern Papua New Guinea

Abstract: A culture-independent examination of microbial diversity in mobile deltaic sediments from the Gulf of Papua, Papua New Guinea, was conducted by sequence analysis of 16S rDNA clone library. Universal small subunit primers were used to amplify DNA extracted from the sediment. Of 91 clones randomly selected from the library, 33 contained unique non-chimeric sequences. Analysis of these unique sequences showed that the majority of them belonged to bacteria (94.5%), with proteobacteria being the dominant division (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Zumft and other researchers reported that ammoniaoxidation should sustain nitrate-reduction [2,28,29,32]. Ammonia-oxidizing and nitrite-oxidizing bacteria have been detected in other anoxic environments by the culturing method (MPN) [26] and nitrite-oxidizing bacteria have been detected in anoxic sediments of the Paci¢c by sequence analysis of the 16S rRNA clone library [27]. We also found that nitrifying bacteria inhabited two reactors operated under anoxic conditions using culturing and nonculturing methods.…”
Section: Community Structure Based On 16s Rdna Analysissupporting
confidence: 52%
“…Zumft and other researchers reported that ammoniaoxidation should sustain nitrate-reduction [2,28,29,32]. Ammonia-oxidizing and nitrite-oxidizing bacteria have been detected in other anoxic environments by the culturing method (MPN) [26] and nitrite-oxidizing bacteria have been detected in anoxic sediments of the Paci¢c by sequence analysis of the 16S rRNA clone library [27]. We also found that nitrifying bacteria inhabited two reactors operated under anoxic conditions using culturing and nonculturing methods.…”
Section: Community Structure Based On 16s Rdna Analysissupporting
confidence: 52%
“…The Kourou^Sinnamary site in French Guiana shares some similar biogeochemical characteristics with tropical Gulf of Papua mobile muds [18], which may help to explain similarities in clone libraries. Although French Guiana and Gulf of Papua libraries do not share closely related low-level taxonomic sequences, the major phylogenetic and physiological groups of bacteria present in these libraries are similar.…”
Section: Discussionmentioning
confidence: 98%
“…KS43f is likely to originate from a sulfate-reducing bacterium, a large number of Q-proteobacterial 16S rDNA sequences (KS25f, KS30, KS38, KS45f, KS72, KS75, KS86, KS90) may have come from potential aerobic sul¢de oxidizers, and several K-proteobacterial sequences (KS12, KS14, KS24) are related to sul¢te oxidizers. The lack in the French Guiana library of 16S rDNA sequences from anaerobic sul¢de-oxidizing O-proteobacteria, found in the Gulf of Papua [18] and Japanese Island sediments [20^22], is noteworthy. The major di¡erence in sulfur cycle reactions in the two mobile mud environments appears to be that oxidation of sulfur species in French Guiana muds is mainly aerobic, whereas both aerobic and anaerobic sul¢de oxidizers are present in the Gulf of Papua muds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria within coastal and shelf sediments play an important role in global biogeochemical cycles, as they are the ultimate sink of most terrestrially derived compounds and a high proportion of marine particle flux. Despite a growing understanding of the global biogeochemical importance of these sediment habitats (Berelson et al, 1990;Blackburn and Blackburn, 1993;Vanduyl et al, 1993;Codispoti et al, 2001), little is known of the bacterial communities inhabiting them (Cifuentes et al, 2000;Todorov et al, 2000;Madrid et al, 2001;Kim et al, 2004), nor the factors influencing their distribution (Bowman et al, 2005;Polymenakou et al, 2005). Marine microbial diversity in the ocean has been the subject of intense recent study (Giovannoni et al, 1990;Fuhrman and Ouverney, 1998;Giovannoni and Rappe, 2000;Venter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%